2000
DOI: 10.1097/00004032-200005000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Chelating Agents for Uranium(vi): 2. Efficacy and Toxicity of Tetradentate Catecholate and Hydroxypyridinonate Ligands in Mice

Abstract: Uranium(VI) (UO2(2+), uranyl) is nephrotoxic. Depending on isotopic composition and dosage, U(VI) is also chemically toxic and carcinogenic in bone. Several ligands containing two, three, or four bidentate catecholate or hydroxypyridinonate metal binding groups, developed for in vivo chelation of other actinides, were found, on evaluation in mice, to be effective for in vivo chelation of U(VI). The most promising ligands contained two bidentate groups per chelator molecule (tetradentate) attached to linear 4- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
141
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 94 publications
(143 citation statements)
references
References 28 publications
1
141
0
1
Order By: Relevance
“…This high affinity is consistent with the relatively relaxed geometry observed in the UO 2 (4Li-Me-3,2-HOPO)(DMSO) crystal structure as well as with the superior ability for 4Li-Me-3,2-HOPO to chelate actinides in vivo. [31,36] Of the rigidly-linked ligands L 6 H 2 -L 8 H 2 , L 6 H 2 is the most acidic, and yet displays the poorest uranyl affinity at all pH. This may be due to the inability to form monomeric uranyl complexes.…”
Section: (L)(oh)] -Complex To Form a [Uo 2 (L)h -2 ] 2-species (Wherementioning
confidence: 99%
See 1 more Smart Citation
“…This high affinity is consistent with the relatively relaxed geometry observed in the UO 2 (4Li-Me-3,2-HOPO)(DMSO) crystal structure as well as with the superior ability for 4Li-Me-3,2-HOPO to chelate actinides in vivo. [31,36] Of the rigidly-linked ligands L 6 H 2 -L 8 H 2 , L 6 H 2 is the most acidic, and yet displays the poorest uranyl affinity at all pH. This may be due to the inability to form monomeric uranyl complexes.…”
Section: (L)(oh)] -Complex To Form a [Uo 2 (L)h -2 ] 2-species (Wherementioning
confidence: 99%
“…Examples of biologically relevant investigations include that of Czerwinski and co-workers that addresses uranyl speciation with the naturally-occuring siderophore desferrioxamine (DFO) [29] as well as those by Durbin and co-workers that examine the in vivo decorporating ability of polybidentate catecholamides and their structural analogs towards the uranyl and transuranic cations. [30][31][32][33] These latter studies revealed that 4-or 5-carbon linear linkers provided optimal decorporating ability to poly-bidentate ligands, but the detailed thermodynamic rationale for this result is relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Several of these ligands are orally active decorporation agents and effective in reducing UO 2 2+ in both kidneys and skeleton (removal efficiency in the sequence MeTAM > CAM(S) > CAM(C) > Me-3,2-HOPO > 1,2-HOPO). 9,[12][13][14] Of the ligands evaluated, the 5LiO-(Me-3,2-HOPO) and 5Li-CAM(S) ligands were identified as low or non-toxic ligands with high efficiency.…”
Section: +mentioning
confidence: 99%
“…Given these issues, the strong binding affinity of MeTAM makes this class of ligands attractive for nuclear waste remediation. Due to the low-toxicity and improved solubility of the 5LiO backbone as shown by previous studies with the 5LiO-(Me-3,2-HOPO) ligand, 14 we prepared the MeTAM analog 5LiO-(MeTAM) (LH 4 , Scheme 2) to study the structures of its uranyl complexes. Herein, we describe the synthesis and characterization of the uranyl complexes with L. Xray crystallography has revealed that [ 4 8-has a helical structure, in which the ligands adopt a bridging coordination mode with two TAM units in each L coordinated to two uranyl ions.…”
Section: +mentioning
confidence: 99%
“…The high affinity for ferric ion of these linear ligands is strongly reflected in their efficacy at removing iron in vivo, as reported elsewhere. 15 …”
Section: Introductionmentioning
confidence: 99%